2017
DOI: 10.1016/j.acvd.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Position paper for the evaluation and management of oral status in patients with valvular disease: Groupe de Travail Valvulopathies de la Société Française de Cardiologie, Société Française de Chirurgie Orale, Société Française de Parodontologie et d’Implantologie Orale, Société Française d’Endodontie et Société de Pathologie Infectieuse de Langue Française

Abstract: Oral health is of particular importance in patients with heart valve diseases because of the risk of infective endocarditis. Recommendations for antibiotic prophylaxis before dental procedures have been restricted, but the modalities of oral evaluation and dental care are not detailed in guidelines. Therefore, a multidisciplinary working group reviewed the literature to propose detailed approaches for the evaluation and management of buccodental status in patients with valvular disease. Simple questions asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 49 publications
0
21
0
5
Order By: Relevance
“…The risks of infectious endocarditis in patients with prosthetic heart valves due to oral infectious foci are well known, with recommendations resulting from the findings of working groups composed of medical doctors and dentists, who recommend twice yearly dental follow-ups for patients with heart disease. 22,23 It is clear that oral bacteria may enter the systemic circulation through discontinuities of epithelium in the periodontal lesion, and several studies have observed these bacteria in blood vessels, within arteriosclerotic plaques or pathological heart valves. 24 Substantial evidence has also been found of the oral origin of bacteria which cause pneumonia 25 and in the subversion of immune cells by periodontopathogens exacerbating the inflammatory response in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The risks of infectious endocarditis in patients with prosthetic heart valves due to oral infectious foci are well known, with recommendations resulting from the findings of working groups composed of medical doctors and dentists, who recommend twice yearly dental follow-ups for patients with heart disease. 22,23 It is clear that oral bacteria may enter the systemic circulation through discontinuities of epithelium in the periodontal lesion, and several studies have observed these bacteria in blood vessels, within arteriosclerotic plaques or pathological heart valves. 24 Substantial evidence has also been found of the oral origin of bacteria which cause pneumonia 25 and in the subversion of immune cells by periodontopathogens exacerbating the inflammatory response in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…3 Kultivačním vyšetřením resekátů chlopní postižených IE bývá zhruba v 50-66 % případů identifi kována typická bakteriální fl óra z dutiny ústní. [5][6][7] Jako původní zdroj bakteriemie se tedy považují především infekční ložiska odontogenního původu. Běžně k bakteriemii dochází při příjmu potravy či orální hygieně.…”
Section: úVodunclassified
“…• devitalizované zuby s rentgenologicky prokazatelným ložiskem u apexu či bez něj (při absenci progrese periapikálního nálezu lze u asymptomatických pacientů přistoupit ke konzervativnímu postupu); • záněty zubní dřeně (akutní i chronická pulpitida); • paradontální choboty a abscesy; • retinované a semiretinované zuby; • odontogenní a neodontogenní cysty; • ponechané zubní kořeny (radix relicta); • záněty čelistních kostí; • chronické sinusitidy; • pokročilé záněty dásní (včetně dásní pod mezičleny můstků a v okolí zubních korunek); • zuby postižené parodontitidou; slizniční ulcerace. 7,8,17,18 Navrhovaný postup 19 Otázka, jak intenzivně a u kterých pacientů přistupovat k sanaci chrupu, doposud nebyla dostatečně zodpovězena a při absenci statisticky významných dat dobře navrhnuté klinické studie zřejmě ani v blízké době zodpovězena nebude. Většina pracovišť v této otázce udržuje status quo a vyžaduje radikální sanaci chrupu při akutních stavech ohrožujících život pacienta.…”
Section: Aspekty Sanace Fokusůunclassified
“…Periodontal diseases go with chronic inflammation [6] that can lead in adulthood to various CVD [3] [4] [5] [6] [7] and reduced, unrestored dentition is associated with increased mortality risk [8] [9]. Oral health has been recognized as a priority by the World Health Organization (WHO) and also the Federation Dentaire Internationale (FDI) leading to define goals [10] [11] It is therefore important to assess the dental health, that could be done using various methods [12] [13] and also for dental practitioner to evaluation the cardiac risk of their patients [14].…”
Section: Introductionmentioning
confidence: 99%